Unit trusts: the ideal investment platform for youth and the newly employed - Mohamed Isa, Zuraidah; Ibrahim, Dahlia; Ahmad Zabib, Zaiful Affendi (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
Mutual funds, sometimes referred to as unit trusts, are a type of collective investment plan that pools the capital of several individuals to buy a variety of securities. As a simple and accessible way to begin investing, this investment vehicle has grown in popularity. Unit trusts have become a popular investment option in Malaysia, particularly among Malaysia's youth and fresh graduates. Early investing is essential for long-term financial stability due to the rising cost of living and the need for financial security. The advantages of unit trusts in the Malaysian setting and their suitability for young and newly employed investors are examined in this article. Future recommendations are also provided to improve the efficacy of investment options.